City of Mirrors: Songs of Lalan Sai, text, translation and commentary by Carol Salomon, edited by Keith E. Cantu and Saymon Zakaria - Lorea, Carola (Religions of South Asia, 2021)
City of Mirrors: Songs of Lalan Sai, text, translation and commentary by Carol Salomon, edited by Keith E. Cantu and Saymon Zakaria. New York: Oxford University Press, 2017. xxxiv + 611 pp., £117.50 (hb). ISBN 9780190680220.